Financial technology and personal financial management: The mediating role of digital financial inclusion - Ana Mufidah; Kamila Nur Afifah; Sumani Sumani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Although financial technology has increased university students’ opportunity to use digital financial services, differences in their financial management behavior show that access alone does cannot guarantee good financial management. Therefore, this study examines whether digital financial inclusion plays a mediating role in association between financial technology and personal financial management. The sample for this research was 370 respondents. Data were analyzed using PLS-SEM. According to the outcomes of the study, there is an effect between financial technology on digital financial inclusion and personal financial management. Digital financial inclusion contributes substantially to personal financial management. Furthermore, digital financial inclusion has been shown to facilitate the relationship between connection between financial technology and personal financial management. This study enriches the literature on personal financial management behaviour, particularly by examining the contribution of financial technology and the mediating role of digital financial inclusion. The practical implication is that advancing digital financial inclusion via enhanced digital infrastructure, user-oriented financial platforms, and financial literacy support from policymakers and fintech providers can facilitate future financial planning and strengthen personal financial management.